2004
DOI: 10.1051/animres:2004034
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of lupin and pea seeds as a substitute for soybean meal in high-producing dairy cow feed

Abstract: -Two experiments were conducted to investigate the substitution of soybean meal by coarsely ground lupin and/or pea seeds in high-producing dairy cow feed. In experiment 1 (Exp. 1), four Holstein dairy cows (35.9 ± 2.2 L·d -1 milk) were put on a control diet consisting of 50% maize silage, 11% grass silage and 36% concentrates on a dry-matter (DM) basis. Soybean meal was partially replaced (75%) by lupin, pea and a mixture (1/1, DM) of lupin and pea on a DM basis, following a 4 × 4 Latin square design. Milk pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
34
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 21 publications
7
34
2
1
Order By: Relevance
“…On the contrary, in our study the blood and milk urea (Tables 3 and 4, respectively) levels in cows appeared to be decreased by the replacement of soybean with pea in concentrates (P=0.04 and P=0.06, respectively). Froidmont and Bartiaux-Thill (2004) found that dietary leguminous grains reduce the level of milk urea in dairy cows due to the low DM and protein intakes. In our study, the blood and milk urea concentrations recorded in cows fed experimental diet were reduced, almost certainly due to a decreased degradability of pea protein leading to a decreased ammonia level in the rumen and urea level in milk and blood, as also reported in a recent study of Volpelli et al (2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, in our study the blood and milk urea (Tables 3 and 4, respectively) levels in cows appeared to be decreased by the replacement of soybean with pea in concentrates (P=0.04 and P=0.06, respectively). Froidmont and Bartiaux-Thill (2004) found that dietary leguminous grains reduce the level of milk urea in dairy cows due to the low DM and protein intakes. In our study, the blood and milk urea concentrations recorded in cows fed experimental diet were reduced, almost certainly due to a decreased degradability of pea protein leading to a decreased ammonia level in the rumen and urea level in milk and blood, as also reported in a recent study of Volpelli et al (2009).…”
Section: Resultsmentioning
confidence: 99%
“…The development of locally grown protein crops may be a solution to improve the valorisation of products and to assure a better traceability of feedstuffs (Froidmont & Bartiaux-Thill 2004).…”
Section: Introductionmentioning
confidence: 99%
“…minor), high protein pea (Pisum sativum L.) and white lupin (Lupinus albus L.) play a fundamental role in organic agriculture and livestock (Siddique et al, 1999) to improve soil fertility (Unkovich et al, 1997;Van Kessel and Hartley, 2000;Ranalli, 2001;Badgley et al, 2007), to close the cycle of nitrogen (Unkovich et al, 2000;Pang and Letey, 2000;Jensen Köpke and Nemecek, 2010) and as protein sources alternative to soybean (Froidmont and Bartiaux, 2004;Jezierny et al, 2010), which could reduce the risk of GMO contamination in the food chain.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of protein in the seeds of the genus Lupinus oscillates between 30 and 45% (Jezierny et al, 2010), and Lupinus species have often been compared with soybean for their protein value (Froidmont and Barthiaux-Hill, 2004). Soybean seed contains 40% protein and 17% lipids, making it a major source of protein and energy (Yin et al, 2011), and it is widely used for animal feed.…”
Section: Introductionmentioning
confidence: 99%